Ozone pollution: What can we see from space? A case study. Issue 3 (8th July 2014) - Foret, G.; Eremenko, M.; Cuesta, J.; Sellitto, P.; Barré, J.; Gaubert, B.; Coman, A.; Dufour, G.; Liu, X.; Joly, M.; Doche, C.; Beekmann, M.
Abstract: Due to its impact on environment, tropospheric ozone received particular attention since several decades. Ground‐based networks associated with regional chemical transport models are used to monitor and forecast surface ozone concentrations, but coverage, representativeness, and accuracy issues remain important. Recent satellite observations have demonstrated the capacity to probe tropospheric ozone, but there has been no explicit attempt to quantify their ability to measure ozone pollution near ground. We propose here to assess the ability of ozone sounders to detect a photochemical ozone pollution event that is supposed to be a favorable situation for satellite detection. We have chosen ozone pollution event over Europe associated with a warm conveyor belt that efficiently transports photochemically produced ozone upward. Ozone satellite products from Global Ozone Monitoring Experiment‐2, Infrared Atmospheric Sounding Interferometer (IASI), and Ozone Monitoring Instrument are analyzed here for their capacity to capture such an event. Also, in situ observations and regional chemical‐transport models show increasing ozone concentrations in the continental and Mediterranean boundary layer and further transport to central Europe and Scandinavia associated with upward transport. Satellite observations do not detect high ozone concentrations within the boundary layer due the weak sensitivity near the surface. Nevertheless, we have shown that the IR sounder IASI was able to detect, qualitatively and quantitatively, the ozone plume transported upward by the warm conveyor belt, suggesting that a quantification of upward transport of ozone pollution could be possible using current satellite observations. This should encourage us to further explore approaches more sensitive to surface ozone (such as the multispectral approach) and to prepare the next generation of still more sensitive spaceborne instruments. Key Point: Ability of satellite to detect ozone pollution is evaluated